Elaboration and investigation on CuO/Pt-TiO2 NTs composite material for supercapacitors applications - ATTOU LOUBABA (Faculté des Sciences de Rabat, 2020)
Metal oxides show promising electronic properties in energy storage applications. The goal of this thesis would be to develop a composite material associating these oxides, then to explore its electronic and electrochemical performance. In the first part, studying theoretically CuO (II) using the FP LAPW method based on DFT with mBJ corrective approach, and experimentally by the effect of the annealing temperature on the properties of the NPs of the CuO produced by the Solgel method. In the second part, fabricating the CPTNT (CuO / Pt-TiO2) composite material from an initial anodic fabrication of the well-ordered TiO2 NTs, sputtering the Pt NPs followed by electrodeposition of the Cu NPs in the material as obtained, followed by oxidation of the copper by thermal annealing. The electrochemical properties and capacitive behavior of this material are evaluated using Cyclic Voltammetry (CV), Electrochemical Impedance Spectroscopy (EIS) and Chronopotentiometry (GCD). A high specific capacity of 423 F g-1 is achieved at a current density of 0.5 A g-1, with long term stability of 93% over 5000 cycles. The results show that this electrode will be able to deliver a high energy density of 19.62 Wh Kg-1 and a power density of up to 442.89 W Kg-1. DFT is used to study the electronic structure of TiO2 codoped by (Cu, Pt), in order to better understand its electrochemical behavior. The results obtained throughout this study demonstrate that this new nanocomposite is a notable candidate for high performance supercapacitors.
Elaboration et étude du matériau composite CuO/Pt-TiO2 NTs pour les applications de supercondensateurs
Keywords: Physics Informatics; Physics Informatics